The Effect of Islamic Financial Literacy, Financial Behavior, and Lifestyle on Impulsive Buying Behavior with Self Control as a Mediating Variable in Generation Z - Fariski Septiansa; Rifa'atul Maftuhah; Tiara Anindya Virana (Ekonomi Bisnis, 2025)
This study aims to examine the influence of Islamic financial literacy, the influence of Islamic financial literacy, financial behavior, and lifestyle on impulsive buying behavior with self-control as a mediating variable in generation Z, with self-control as a mediating variable. The method used is a quantitative approach with the Partial Least Square Structural Equation Modeling (PLS-SEM) technique through the SmartPLS 4.0 application. Data was collected from 250 students of the Sharia Banking, Management, and Accounting Study Program at the University of Muhammadiyah Surabaya. The results of the study show that self-control has a significant effect on financial behavior. However, Islamic financial literacy, financial behavior, and lifestyle do not have a significant effect on impulse buying behavior, either directly or indirectly through self-control. In addition, the entire mediation pathway through self-control is also insignificant. However, Islamic financial literacy shows the direction of a negative relationship with impulsive behavior. The R-square value shows that the model is able to explain 96% of variance in financial behavior, but only 5.4% for impulse buying behavior. These findings emphasize that Generation Z's consumptive behavior is more influenced by emotional and digital factors, so a more contextual, interactive, and appropriate Islamic financial education strategy is needed.